CNIH4 Interacts with Newly Synthesized GPCR and Controls Their Export from the Endoplasmic Reticulum. (6th February 2014) - Sauvageau, Etienne; Rochdi, Moulay D.; Oueslati, Morad; Hamdan, Fadi F.; Percherancier, Yann; Simpson, Jeremy C.; Pepperkok, Rainer; Bouvier, Michel
<x xml:space="preserve">Abstract</x> The molecular mechanisms regulating G protein‐coupled receptors (GPCRs) trafficking from their site of synthesis in the endoplasmic reticulum (ER) to their site of function (the cell surface) remain poorly characterized. Using a bioluminescence resonance energy transfer‐based proteomic screen, we identified a novel GPCR‐interacting protein; the human cornichon homologue 4 (CNIH4). This previously uncharacterized protein is localized in the early secretory pathway where it interacts with members of the 3 family of GPCRs. Both overexpression and knockdown expression of CNIH4 caused the intracellular retention of GPCRs, indicating that this ER‐resident protein plays an important role in GPCR export. Overexpression of CNIH4 at low levels rescued the maturation and cell surface expression of an intracellularly retained mutant form of the β2‐adrenergic receptor, further demonstrating a positive role of CNIH4 in GPCR trafficking. Taken with the co‐immunoprecipitation of CNIH4 with Sec23 and Sec24, components of the COPII coat complex responsible for ER export, these data suggest that CNIH4 acts as a cargo‐sorting receptor, recruiting GPCRs into COPII vesicles. <inline-graphic xlink:href="ark:/27927/pgg4swwqjvq" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />